Impact of antidiabetic treatment with dipeptidyl peptidase-4 inhibitors on the risk of cardiac arrhythmias among patients with type 2 diabetes mellitus. (14th October 2021) - Boulmpou, A; Patoulias, D; Teperikidis, E; Tsavousoglou, C; Vergopoulos, S; Toumpourleka, M; Doumas, M; Fragakis, N; Vassilikos, V; Papadopoulos, C E
Abstract: Introduction: Type 2 diabetes mellitus (T2DM) is considered as a global pandemic, comprising a significant, independent cardiovascular risk factor. Besides major adverse cardiovascular events, patients with T2DM experience an increased risk of heart rhythm disorders, nevertheless the exact mechanisms of arrhythmogenesis in the context of diabetes mellitus are still being under investigation. Dipeptidyl peptidase-4 (DPP-4) inhibitors represent a novel class of antidiabetic regimens with proved safety and efficacy among patients with T2DM and a series of randomized controlled trials (RCTs) addressing cardiovascular outcomes with DPP-4 inhibitors have been published. The exact effect of DPP-4 inhibitors on the arrhythmic burden among diabetic individuals is yet to be identified. Purpose: In the present meta-analysis, we sought to determine the impact of antidiabetic treatment with DPP-4 inhibitors on the risk of various cardiac arrhythmias. Methods: We searched PubMed for all published RCTs assessing cardiovascular outcomes after antidiabetic treatment with DPP-4 inhibitors. We extracted data regarding the risk for the following cardiac arrhythmias: atrial fibrillation, atrial flutter, atrial tachycardia, ventricular fibrillation, ventricular tachycardia, ventricular extrasystoles, supraventricular tachycardia, sinus node dysfunction, second degree atrioventricular block, complete atrioventricular block. Results: Following a meticulous assessment of the available literature, we pooled data from 6 trials in a total of 52, 520 patients. Antidiabetic treatment with DPP-4 inhibitors did not significantly affect the risk for atrial fibrillation (RR=0.95, 95% CI: 0.78–1.17, I 2 =0%) (Figure 1a). Of note, DPP-4 inhibitors were associated with a significant increase in the risk for atrial flutter, equal to 52% (RR=1.52, 95% CI: 1.03–2.24, I 2 =0%), as shown in Figure 2. Finally, DPP-4 inhibitors did not have a significant impact on the risk for any of the rest assessed major cardiac arrhythmias. Conclusions: DPP-4 inhibitors do not seem to be associated with a significant risk for any major cardiac arrhythmias, except for atrial flutter. Funding Acknowledgement: Type of funding sources: None.